Oxygen availability and distance to surface environments determine community composition and abundance of ammonia‐oxidizing prokaroytes in two superimposed pristine limestone aquifers in the Hainich region, Germany. Issue 1 (9th July 2014) - Opitz, Sebastian; Küsel, Kirsten; Spott, Oliver; Totsche, Kai Uwe; Herrmann, Martina
Abstract We followed the abundance and compared the diversity of ammonia‐oxidizing archaea (AOA) and bacteria (AOB) in the groundwater of two superimposed pristine limestone aquifers located in the Hainich region (Thuringia, Germany) over 22 months. Groundwater obtained from the upper aquifer (12 m depth) was characterized by low oxygen saturation (0–20%) and low nitrate concentrations (0–20 μM), contrasting with 50–80% oxygen saturation and 40–200 μM nitrate in the lower aquifer (48 m and 88 m depth). Quantitative PCR targeting bacterial and archaeal amoA and 16S rRNA genes suggested a much higher ammonia oxidizer fraction in the lower aquifer (0.4–7.8%) compared with the upper aquifer (0.01–0.29%). In both aquifers, AOB communities were dominated by one phylotype related to Nitrosomonas ureae, while AOA communities were more diverse. Multivariate analysis of amoA DGGE profiles revealed a stronger temporal variation of AOA and AOB community composition in the upper aquifer, pointing to a stronger influence of surface environments. Parallel fluctuations of AOA, AOB, and total microbial abundance suggested that hydrological factors (heavy rain falls, snow melt) rather than specific physicochemical parameters were responsible for the observed community dynamics.